Efficiency improvement in standalone solar PV water pumping system by pulsating pump operation based on intermediate supercapacitor buffer - Yurii Biletskyi; Ihor Shchur (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
One of the promising ways of using solar energy to generate low-power electricity is standalone solar PV water pumping systems (SPVWPS) designed for irrigation and urban/rural water supplies. The simplest and most common among such SPVWPSs are direct driven systems, which do not have expensive and unreliable batteries. This paper investigates the basic traditional configuration that consists of a PV module, a DC-DC converter performing its maximum power point tracking (MPPT), and a brushless DC motor (BLDCM) driving a centrifugal pump (CP). The conducted simulation studies on the developed model in the SimScape multiphysical library of the Matlab/Simulink environment shows that such a direct driven SPVWPS is characterized by a very low overall efficiency, and its operating range of solar irradiance starts from only 450 W/m2. Taking into account that the water pumping process itself is an accumulation of energy, this work proposes applying a pulsating mode of pump operation with nominal power in each pulse enabled by the introduction of an intermediate supercapacitor buffer. It is permanently connected to the PV module and periodically connected to the BLDCM with the CP using an electronic switch. The on-off algorithm of this switch operation is designed in such a way as to ensure the MPPT of the PV module. In the paper, the operation regularities of the SPVWPS of the proposed configuration were investigated, and the method of determining its operating parameters was developed. The conducted simulation studies showed that the pulsating operation of the proposed SPVWPS provides a constant maximum value of total system efficiency across the entire range of solar irradiance. The water pumping performance of the investigated hydraulic system during a sunny summer day in the latitudes of Ukraine in the proposed SPVWPS is on 64 % higher than in the SPVWPS of basic traditional configuration. Experimental studies conducted on the created SPVWPS sample confirmed the effectiveness of the proposed pulsating operation of the CP: in conditions of reduced insolation, the efficiency of the operation of the CP together with its electric drive was 25 % higher than in the basic configuration.